Low-carbon development in remote Indigenous communities: Applying a community-directed model to support endogenous assets and aspirations. Issue 95 (May 2019) - Stewart, J.; Anda, M.; Harper, R.J.
Highlights: A community-directed decision-support model for low-carbon development is applied with two remote Australian Indigenous communities. Efficiency and sharing strategies already exist, so a supportive approach to endogenous initiatives is needed, rather than "behaviour change". A strategic asset management approach would be more beneficial than short-term training and service delivery. Partnerships and positioning within regional planning directives would facilitate long-term development strategies. Communities' multi-asset investments in traditional lands, provide opportunities for climate change mitigation and economic development. Abstract: Remote Indigenous communities in Australia, which are generally small and widely distributed across the continent, face several socio-economic disadvantages. Yet, there are also many successful examples of Indigenous-led enterprises and initiatives in these locations. A history of top-down government policies pertaining to these communities has led to calls for improved engagement with residents regarding economic development, service delivery and climate change vulnerability. At the same time, increased carbon emissions are likely to ensue from economic development efforts if not planned carefully. This article proposes a community-directed approach, the Resilient Communities and Livelihoods Asset Integration Model (ReCLAIM) to achieve low-carbon development in line with the United Nations Sustainable Development Goals. The design of the model is outlined, along with the results of applying the first step of the model, an asset and aspirations identification workshop, with two remote Indigenous communities in Australia. The results of the first workshop indicate that residents in these communities are already applying efficiency, resource-sharing and other strategies to limit resource use. Therefore, the focus in these communities should be on assisting and enhancing outcomes of these endogenous strategies, rather than the behaviour change approach that has often been applied within low-carbon programmes. Behavioural efficiency measures alone will also provide little impact, without commensurate changes to building design and energy supply systems. Both communities had a diversity of assets to employ towards mitigation strategies and development aspirations, although deficiencies in funding, resourcing and long-term working partnerships were also identified. Selection criteria to screen potential strategies were developed from workshop responses, and the process would be applicable to similar communities, globally.